Ankylosis management with autogenous grafts: A systematic review - Sujata Mohanty; Anjali Verma (Elsevier, 2021)
A systematic review was performed to assess the clinical outcomes of the reconstructive methods using autogenous grafts for the management of temporomandibular joint (TMJ) ankylosis A comprehensive electronic and manual search of the literature without date or language restriction was performed in January 2021 to identify randomized controlled trials, prospective, and retrospective studies with the aim of comparing the various surgical modalities for TMJ ankylosis. Twenty-six publications were included: prospective (n ​= ​17), retrospective (n ​= ​7), randomised control trial (n ​= ​1) and ambispective study (n ​= ​1). Costochondral graft was the most common graft used followed by Coronoid process graft. Meta-analysis was not possible as most of studies were non-controlled in nature. Based on the available data, there was a strong evidence that autogenous grafts especially Costochondral grafts and coronoid grafts have remained one of the most favoured methods of reconstruction. Prospective and randomized control studies are recommended for the best stratification for the use of autogenous grafts for the management of TMJ ankylosis.